Nanoparticles in Bi0.5Sb1.5Te3: A prerequisite defect structure to scatter the mid-wavelength phonons between Rayleigh and geometry scatterings. (15th February 2020) - Lee, Kyu Hyoung; Kim, Hyun-Sik; Shin, Weon Ho; Kim, Se Yun; Lim, Jae-Hong; Kim, Sung Wng; Kim, Sang-il
Abstract : Nanoparticles in thermoelectric alloys has been considered as one of the most important ingredients to enhance their thermoelectric figure of merit zT mainly by reducing the lattice thermal conductivity due to intensified phonon scattering. However, the scattering mechanism of phonon with respect to wavelengths, which provides the comprehensive design rules for nanocomposites with enhanced zT, has not been fully understood. Here, we report a critical role of nanoparticles for the lattice thermal conductivity reduction from the theoretical and experimental analysis of the temperature-dependent thermal and electronic transport properties of p -type Ag/Cu nanoparticles-embedded Bi0.5 Sb1.5 Te3 with respect to their electronic, bipolar, and lattice thermal conductivities. It was found that the introduction of the Ag/Cu nanoparticles reduced the lattice thermal conductivity through the additional phonon scattering based on the changeover between the Rayleigh and geometrical scatterings, indicating the indispensability of nanoparticles to scatter phonons that cannot be scattered effectively by either point defects or grain boundaries. Graphical abstract: Image, graphical abstract